The Effect of Virgin Coconut Oil (VCo) in Reducing Diaper Rash in Children with Acute Gastroenteritis - Pangesti, Nova Ari; Riyanti, Eko; Maulana, Fahreza Alif (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Acute gastroenteritis (GEA) is one of the diseases in developing countries that is the main cause of morbidity and mortality in children. Gastroenteritis resulting in Diaper rush causes a bright red rash caused by red skin irritation exposed to urine or feces that occurs for a long time on the bottom of the child's diaper. Diapers experienced by children will be at risk of causing pain, itching, and affecting discomfort because they can also spread to the genital area. Therefore, a safe intervention is needed that can reduce Diaper rush. Objective: To determine the Effect of Virgin Coconut Oil (VCO) in reducing diaper rash in Children with Acute Gastroenteritis. Method: This study is a case study involving 2 child patient participants aged 2-36 months with a medical diagnosis of acute gastroenteritis who have nursing problems of skin integrity disorders with moderate redness. Results: on the first day of the client, the redness on the buttocks looked moderate with a score of 4, on the 2nd day the child's redness looked mild with a score of 2, and on the 3rd day the child was advised to go home by the doctor because the condition had improved and the redness on the buttocks had decreased. In client 2 on day 1 the client's redness looked moderate with a score of 4, and on day 2 the client's redness still looked moderate with a score of 3, and on day 3 the redness on the client's buttocks looked mild with a score of 2 there were changes in both clients improving from the first day to the second and third days. Conclusions: Virgin coconut oil therapy is effective in treating diaper rash in pediatric patients by increasing skin moisture and accelerating the growth of granulation tissue and reducing redness.